2020
DOI: 10.1021/acs.jpcc.9b11441
|View full text |Cite
|
Sign up to set email alerts
|

Stone–Wales Defect Induced Performance Improvement of BC3 Monolayer for High Capacity Lithium-Ion Rechargeable Battery Anode Applications

Abstract: First-principles density functional theory (DFT) computations were adopted to assess the potential application of a boron carbide (BC 3 ) monolayer with point and topological defects as an anode material in alkali metal-based lithium (Li) ion rechargeable batteries. Results show that point defects (mono and bi vacancies) induce a large structural deformation upon Li intercalation which restricts their use for anode application. However, the Stone−Wales defect filled BC 3 monolayer shows high structural stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 74 publications
2
48
0
Order By: Relevance
“…[ 10 ] The transition metal‐based Titanium Carbide (Ti 2 C) and its F, O, and OH surface terminated Ti 2 CT 2 (T = F − , O − , OH − ) MXenes have been experimentally synthesized and suitable for many potential applications. [ 3,11,12 ] Similar to other 2D materials and heterostructures, [ 13,14 ] defect formation is inevitable in synthesizing of MXenes, [ 15 ] and defects can rigorously alter their electronic, mechanical, and magnetic properties. [ 16–19 ] The presence of defects can be beneficial [ 13,14,16 ] or unfavorable [ 18 ] for different properties and/or applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 ] The transition metal‐based Titanium Carbide (Ti 2 C) and its F, O, and OH surface terminated Ti 2 CT 2 (T = F − , O − , OH − ) MXenes have been experimentally synthesized and suitable for many potential applications. [ 3,11,12 ] Similar to other 2D materials and heterostructures, [ 13,14 ] defect formation is inevitable in synthesizing of MXenes, [ 15 ] and defects can rigorously alter their electronic, mechanical, and magnetic properties. [ 16–19 ] The presence of defects can be beneficial [ 13,14,16 ] or unfavorable [ 18 ] for different properties and/or applications.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3,11,12 ] Similar to other 2D materials and heterostructures, [ 13,14 ] defect formation is inevitable in synthesizing of MXenes, [ 15 ] and defects can rigorously alter their electronic, mechanical, and magnetic properties. [ 16–19 ] The presence of defects can be beneficial [ 13,14,16 ] or unfavorable [ 18 ] for different properties and/or applications. Although there are some reports on the defect analysis in different types of MXenes by theoretical and experimental methods, [ 20–22 ] a detailed analysis is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…From the theoretical investigations, it was seen that the SW defects in 2D materials significantly alter the electronic properties such as fast charge transfer and display most active sites for metal-ions adsorptions. [136,[142][143][144][145] Recently it was reported that the SW defect significantly enhanced the electrochemical performance of Li-ion battery. [136] Figure 3 a (I-IV) shows the BC 3 monolayer with pristine and SW defected sheet.…”
Section: Sà W Defects For Mibsmentioning
confidence: 99%
“…[136,[142][143][144][145] Recently it was reported that the SW defect significantly enhanced the electrochemical performance of Li-ion battery. [136] Figure 3 a (I-IV) shows the BC 3 monolayer with pristine and SW defected sheet. When the Li-atom located at the top of the pristine BC 3 surface then the adsorption energy are varies from � À 0.3 eV to À 0.90 eV.…”
Section: Sà W Defects For Mibsmentioning
confidence: 99%
See 1 more Smart Citation